Rural School in Spain: Between Compensatory Education and Inclusive Education - Boix-Tomàs, Roser (2015)
Education legislation in Spain has been a constant shift between the ruling political parties. Seven school laws have been legislated throughout 35 years of democracy, and that is one of the main issues Spanish education has faced in order to achieve adequate quality levels. And rural schools have not remained unaffected to this continuous swinging; basically, rural schools have been legislated from the perspective of compensatory education, whereas the vision of inclusive education within a framework of a diverse context aimed to effectively reduce barriers to learning and participation has been scarcely approached. In order to achieve that goal, political stability is needed, a major State Pact which is not foreseen at the present time.